2016
DOI: 10.1177/0892705714563116
|View full text |Cite
|
Sign up to set email alerts
|

Number of processing cycle effect on the properties of the composites based on alfa fiber

Abstract: The objective of the investigation described in this work was to study the reprocessing effects on the alfa fiber reinforced polyvinylchloride composites with and without maleic anhydride-grafted polyvinyl chloride used as compatibilizer. The material was characterized after each extrusion using tensile tests, scanning electron microscopy (SEM), dynamic mechanical, and thermal analysis. Results indicated that generally after four cycles, the recycled composites had considerably higher modulus as compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…A decrease in fibre length during reprocessing was found for all cited studies. An opposite trend was observed for the void fraction, which was observed to decrease during reprocessing, leading to a more homogeneous composite structure and a better wetting of the fibres within the matrix [12,13]. The main problem which appears during reprocessing is the shortening of fibres, leading to a lower aspect ratio when single man-made fibres are considered.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…A decrease in fibre length during reprocessing was found for all cited studies. An opposite trend was observed for the void fraction, which was observed to decrease during reprocessing, leading to a more homogeneous composite structure and a better wetting of the fibres within the matrix [12,13]. The main problem which appears during reprocessing is the shortening of fibres, leading to a lower aspect ratio when single man-made fibres are considered.…”
Section: Introductionmentioning
confidence: 85%
“…This phenomenon was observed by different authors for different natural fibre bundles in variable matrices, eg. for flax/PLA [9], flax/PP [4,8], hemp/PP [2,3], sisal/PP [2,3], wood fibre/PP [4] or alfa fibre/PVC [12]. Nevertheless, the fibre bundle may be damaged with an increasing number of recycling steps, especially if the fibre bundles are already split into single fibres, leading to lower mechanical composite characteristics as a consequence of reprocessing [2,3].…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…As to PP based eco-composites, it is generally expected to have less recyclability than the pure PP because of the heterogeneous and the inherent lower thermal stability of natural fibres. Despite these difficulties, several research works have been interested in recycling natural fibres reinforced polymer composites [5][6][7][8][9]. For example, Bourmaud and Baley [5] studied the mechanical and thermo-physical behaviour of recycled short hemp and sisal fibres reinforced PP.…”
Section: Introductionmentioning
confidence: 99%
“…About alfa fibre reinforced polymer, few researchers studied the effect of recycling on their mechanical properties. To the author's knowledge, only one study was conducted by Hammiche et al [8]. They showed that the tensile strength and Young's modulus of short alfa fibre reinforced polyvinylchloride were enhanced after four recycling cycles.…”
Section: Introductionmentioning
confidence: 99%